Metal Sulfides Yolk–Shell Nanoreactors with Dual Component for Enhanced Acidic Electrochemical Hydrogen Production. Issue 3 (18th November 2022) - Liu, Yuheng; Gong, Lihua; Zhang, Yonghui; Wang, Peiyuan; Wang, Guoqing; Bai, Fenghua; Zhao, Zhenting; Gong, Feilong; Liu, Jian
Abstract : The activity of electrocatalysts can be optimized via constructing heterostructures, while it remains a challenge for the universal synthesis of heterocatalysts with covalent interface. Herein, a universal bifunctional‐S strategy for the preparation of covalently connected metal sulfides yolk–shell nanoreactors with dual components toward enhanced electrochemical hydrogen production in acid, is reported. Specifically, the yolk–shell MoS2 ‐(CTAB)2 S z host with abundant covalent S2 2− is first developed by a micelle‐confined microemulsion technology. The preencapsulated S2 2− in the precursor is utilized to in situ react with the additional M ions (M = Fe, Co, Ni, Cu, Zn, Mn, Cd, Sn), thus creating the covalent microenvironment at the heterointerface, which demonstrates a universal strategy to prepare dual‐component metal sulfides nanoreactors (MoS2 /M x S y –BS). The resultant MoS2 /CdS–BS nanoreactor exhibits excellent hydrogen evolution activity (27 mV at 10 mA cm − 2 ) among the MoS2 ‐based heterocatalysts reported in the literature, while representing an improvement of four times than that of as‐prepared traditional MoS2 /CdS heterocatalyst. Operando X‐ray diffractometer patterns are performed to study durability. The enhanced mechanism related to the transformation of catalytic center and the establishment of "electronic bridge" at the interface of MoS2 /CdS–BS are revealed by theoretical calculations. This study inspires to develop covalently connected electrocatalysts via nanoreactors' engineering. Abstract : A universal bifunctional‐S assisted strategy is proposed for the preparation of covalently connected dual‐component metal sulfide yolk–shell nanoreactors. Benefitting from the unique configuration and covalent heterointerface, optimized MoS2 /CdS–BS presents much better hydrogen evolution activity than traditional MoS2 /CdS and reported MoS2 ‐based heterocatalysts. Density functional theory calculations reveal that the enhanced activity is attributed to the "electronic bridge" and transformational catalytic center.